Non-marital relationships and The European Court of Human Rights - Dias, Cristina (2018)
The European Court of Human Rights (ECtHR) has been making a wide interpretation of the concept of family life, which comprises not only the traditional family relationships, but also non-marital ones. The concepts of private life and family life, in the light of Art. 8 of the European Convention on Human Rights (ECHR), acknowledges other family forms. This study is about registered partnership or de facto relationship. There are quite substantial differences regarding legal regimes throughout Europe - for instance, the French regime («Du Pacte Civil de Solidarité») is quite distinct from the German («Die Eingetragene Lebenspartnerschaft»)3, the Portuguese («Regime de Proteção das Uniões de Facto») or the British («Civil Partnership Act»). Therefore, a reflection on the state of the art of these family forms and its’ interpretation in the ECtHR will undoubtedly be enriched with a critical perspective and some comparative law study